Evaluation of Chitosan/Alginate Beads Using Experimental Design: Formulation and In Vitro Characterization - Takka, Sevgi (Springer US, 2010)
Bovine serum albumin-loaded beads were prepared by ionotropic gelation of alginate with calcium chloride and chitosan. The effect of sodium alginate concentration and chitosan concentration on the particle size and loading efficacy was studied. The diameter of the beads formed is dependent on the size of the needle used. The optimum condition for preparation alginate–chitosan beads was alginate concentration of 3% and chitosan concentration of 0.25% at pH 5. The resulting bead formulation had a loading efficacy of 98.5% and average size of 1,501 μm, and scanning electron microscopy images showed spherical and smooth particles. Chitosan concentration significantly influenced particle size and encapsulation efficiency of chitosan–alginate beads (p < 0.05). Decreasing the alginate concentration resulted in an increased release of albumin in acidic media. The rapid dissolution of chitosan–alginate matrices in the higher pH resulted in burst release of protein drug.